Mitochondrial Effects of PGC-1alpha Silencing in MPP+ Treated Human SH-SY5Y Neuroblastoma Cells - Ye, Qinyong; Chen, Chun; Si, Erwang; Cai, Yousheng; Wang, Juhua; Huang, Wanling; Li, Dongzhu; Wang, Yingqing; Chen, Xiaochun (Frontiers in Molecular Neuroscience, 2017)
The dopaminergic neuron degeneration and loss that occurs in Parkinson’s disease (PD) has been tightly linked to mitochondrial dysfunction. Although the aged-related cause of the mitochondrial defect observed in PD patients remains unclear, nuclear genes are of potential importance to mitochondrial function. Human peroxisome proliferator-activated receptor γ coactivator-1alpha (PGC-1α) is a multi-functional transcription factor that tightly regulates mitochondrial biogenesis and oxidative capacity. The goal of the present study was to explore the potential pathogenic effects of interference by the PGC-1α gene on MPP+-induced SH-SY5Y cells. We utilized RNA interference (RNAi) technology to probe the pathogenic consequences of inhibiting PGC-1α in the SH-SY5Y cell line. Remarkably, a reduction in PGC-1α resulted in the reduction of mitochondrial membrane potential, intracellular ATP content, and intracellular H2O2 generation, leading to the translocation of cytochrome c to the cytoplasm in the MPP+-induced PD cell model. The expression of related proteins in the signaling pathway (e.g., ERRα, NRF-1, NRF-2, and PPARγ) also decreased. Our finding indicates that siRNA interference targeting the PGC-1α gene could inhibit the function of mitochondria in several capacities and that the PGC-1α gene may modulate mitochondrial function by regulating the expression of ERRα, NRF-1, NRF-2 and PPARγ. Thus, PGC-1α can be considered a potential therapeutic target for PD.